Responding to COVID-19: Learning from program adaptation in Malawi - Kumchulesi, Grace; Babu, Suresh Chandra; Patterson, Andrew; Malunga, Anthony; Ranaivoarivelo, Nivo (CARE Malawi, 2021)
This learning brief captures the experience of a large Resilience Food Security Activity, USAID – Titukulane, in responding to COVID-19 in Malawi. The brief includes challenges associated with the response and how Titukulane will adapt to unforeseeable shocks in its programming and implementation based on learning from the COVID-19 response.